Impella versus VA-ECMO for the treatment of patients with cardiogenic shock: the Impella Network Project – observational study protocol for cost-effectiveness and budget impact analyses - Pierluigi Stefàno; Rosanna Tarricone; Mauro Pennacchi; Serafina Valente; Anna Mara Scandroglio; Mario Iannaccone; Carla Rognoni; Giuseppe Tarantini; Italo Porto; Davide Pacini; Antonio Loforte; Gino Gerosa; et al. (BMJ Open, 2024)
Introduction The treatment of patients with cardiogenic shock (CS) encompasses several health technologies including Impella pumps and venoarterial extracorporeal membrane oxygenation (VA-ECMO). However, while they are widely used in clinical practice, information on resource use and quality of life (QoL) associated with these devices is scarce. The aim of this study is, therefore, to collect and comparatively assess clinical and socioeconomic data of Impella versus VA-ECMO for the treatment of patients with severe CS, to ultimately conduct both a cost-effectiveness (CEA) and budget impact (BIA) analyses.Methods and analysis This is a prospective plus retrospective, multicentre study conducted under the scientific coordination of the Center for Research on Health and Social Care Management of SDA Bocconi School of Management and clinical coordination of Istituto di Ricovero e Cura a Carattere Scientifico (IRCCS) San Raffaele Scientific Institute in Milan. The Impella Network stemmed for the purposes of this study and comprises 17 Italian clinical centres from Northern to Southern Regions in Italy. The Italian network qualifies as a subgroup of the international Impella Cardiac Surgery Registry. Patients with CS treated with Impella pumps (CP, 5.0 or 5.5) will be prospectively recruited, and information on clinical outcomes, resource use and QoL collected. Economic data will be retrospectively matched with data from comparable patients treated with VA-ECMO. Both CEA and BIA will be conducted adopting the societal perspective in Italy. This study will contribute to generate new socioeconomic evidence to inform future coverage decisions.Ethics and dissemination As of May 2024, most of the clinical centres submitted the documentation to their ethical committee (N=13; 76%), six centres received ethical approval and two centres started to enrol patients. Study results will be published in peer-reviewed publications and disseminated through conference presentations.